Sociomateriality in Action: Theorizing Change in Sociomaterial Practices of Working from Home - Waizenegger, Lena; Schaedlich, Kai; Doolin, Bill (Springer, 2023)
The COVID-19 pandemic has led to an enforced ‘big bang’ adoption of working from home, involving the rapid implementation and diffusion of digital collaboration technologies. This radical shift to enforced working from home led to substantial changes in the practice of work. Using a qualitative research approach and drawing on the interview accounts of 29 knowledge workers required to work from home during the pandemic, the study identified five sociomaterial practices that were significantly disrupted and required reconfiguration of their constitutive social and material elements to renew them. The paper further shows evidence of the ongoing evolution of those sociomaterial practices among the participants, as temporary breakdowns in their performance led to further adjustments and fine-tuning. The study extends the body of knowledge on working from home and provides a fine-grained analysis of specific complexities of sociomaterial practice and change as actors utilize conceptual and contextual sensemaking to perceive and exploit possibilities for action in their unfolding practice of work. Against the backdrop of the increasing adoption of hybrid working in the aftermath of the pandemic, the paper offers four pillars derived from the findings that support the establishment of a conducive working from home environment.
Keywords: 0806 Information Systems; 1503 Business and Management; Information Systems; 3503 Business systems in context; 4609 Information systems